The four-factor personality model and its qualitative correlates among opioid agonist therapy clients - Mahu, Ioan T.; Conrod, Patricia J.; Barrett, Sean P.; Sako, Aïssata; Swansburg, Jennifer; Stewart, Sherry H. (Frontiers in Psychiatry, 2023)
Background: The Four Factor Personality Vulnerability model (Castellanos-Ryan and Conrod, 2012) identifies four specific personality traits (e.g., sensation seeking [SS], impulsivity [IMP], anxiety sensitivity [AS], and hopelessness [HOP]) as implicated in substance use behaviours, motives for substance use, and co-occurring psychiatric conditions. Although the relationship between these traits and polysubstance use in opioid agonist therapy (OAT) clients has been investigated quantitatively, no study has examined the qualitative expression of each trait using clients’ voice. Method: Nineteen Methadone Maintenance Therapy (MMT) clients (68.4% male, 84.2% white, mean age[SD] = 42.71 [10.18]) scoring high on one of the four personality traits measured by the Substance Use Risk Profile Scale (SURPS; Woicik et al., 2009) completed a semi-structured qualitative interview designed to explore their lived experience of their respective trait. Thematic analysis (Braun and Clarke, 2006) was used to derive themes, which were further quantified using content analysis (Elo and Kyngäs, 2008). Results: Themes emerging from interviews reflected (1) internalizing and externalizing symptoms, (2) adversity experiences, and (3) polysubstance use. Internalizing symptoms subthemes included symptoms of anxiety, fear, stress, depression, and avoidance coping. Externalizing subthemes included anger, disinhibited cognitions, and anti-social and risk-taking behaviors. Adverse experiences subthemes included poor health, poverty, homelessness, unemployment, trauma, and conflict. Finally, polysubstance use subthemes include substance types, methods of use, and motives. Differences emerged between personality profiles in the relative endorsement of various subthemes, including those pertaining to polysubstance use, that were largely as theoretically expected. Conclusion: Personality is associated with unique cognitive, affective, and behavioral lived experiences, suggesting that personality may be a novel intervention target in adjunctive psychosocial treatment for those undergoing OAT.